THE INFLUENCE OF MODIFIERS ON INCREASING THE DURABILITY OF ASPHALT CONCRETE PAVEMENTS - Akhmedov Akhadjian Urmonjonovich (Western European Studies, 2025)
This article shows the use of increasing the durability of modified asphalt concrete formed with the addition of polymers " Kraton D1186" and surface-forming additives SFM "SP-OEP" with long-term water saturation, which is influenced by the main parameters of asphalt concrete, concrete is also considered in terms of frost resistance, corrosion resistance and crack resistance.
Keywords: Kraton D1186; water resistance; cracking resistance